Social Psychology - Franzoi, Stephen L. (New York [etc.] McGraw-Hill, 2008)
This title presents readable research. This distinctive, theory-driven text uses 'The Self' as a theme to give students a meaningful context for exploring the key concepts of social psychology. 'Applications' sections have been incorporated into most chapters, and 'Featured Study' sections at the end of every chapter summarize the purpose, method, and results of recently published scientific articles. Retaining the emphasis on methodology, the text also continues the tradition of strong gender coverage, while expanding the coverage of social cognition and social neuroscience
Keywords: Psicología social